Perlindungan Lahan Pertanian Pangan Berkelanjutan (PLP2B) di Kabupaten Karawang: Sebuah Tinjauan Tentang Collaborative Governance - Dede Badrudin; Dadan Kurniansyah; Mochamad Faizal Rizki (Peneliti.net, 2022)
This study discusses Collaborative Governance in the policy of Protecting Sustainable Food Agricultural Land in Karawang Regency. The purpose of this study is to examine the process of Collaborative Governance in the formulation and implementation of policies for the Protection of Sustainable Food Agricultural Land in Karawang Regency. This study uses a descriptive research method with a qualitative approach. Data collection was carried out through Sugiyono's triangulation (2018) which included interviews, observations and documentation studies. Then the data was analyzed using the concept of data analysis by Miles and Huberman (1982) which has stages of reduction, presentation and then drawing conclusions. This study was analyzed using Collaborative Governance Theory expressed by Stephen Balogh et al (2012) with three dimensions, namely Collaboration Dynamics, Actions, and Impacts & Adaptations. The results of research on Collaborative Governance in the policy of Protecting Sustainable Food Agricultural Land in Karawang Regency succeeded in producing Regional Regulation No. 1 of 2018 concerning the Protection of Agricultural Land for Sustainable Food, but it still reflects that the collaboration process only involves government actors so that the resulting policy framework still has some resistance from farmers who made the Regent's Regulation as the implementing regulation of Perda No. 1 of 2018 late to be published.